2020
DOI: 10.1017/jfm.2019.1007
|View full text |Cite
|
Sign up to set email alerts
|

Shape design for stabilizing microparticles in inertial microfluidic flows

Abstract: Design of microparticles which stabilize at the centerline of a channel flow when part of a dilute suspension is examined numerically for moderate Reynolds numbers (10 ≤ Re ≤ 80). This problem is motivated by the need for design of shaped particle carriers for use in next generation cell cytometry devices. Stability metrics for particles with arbitrary shapes are formulated based on linear-stability theory. Particle shape is parametrized by a compact, Non-Uniform Rational B-Spline (NURBS)-based representation.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It has also previously been shown, both computationally and experimentally, that the shape of rigid particles can influence their migration patterns in a microchannel (43)(44)(45)(46). It is quite likely that it will similarly affect deformable particles such as cells.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has also previously been shown, both computationally and experimentally, that the shape of rigid particles can influence their migration patterns in a microchannel (43)(44)(45)(46). It is quite likely that it will similarly affect deformable particles such as cells.…”
Section: Introductionmentioning
confidence: 94%
“…Adherent MCF-7 cells appear rounded in shape, whereas MDA-MB-231 cells are more elongated in one direction and therefore spindle-shaped. It has been hypothesized that deformable particles suspended in flow experience stresses that can cause it to change its shape (14,47), and therefore, it may also affect the cells' inertial positions; however, some of the above studies have shown that centerline-focusing particles typically have fore-aft asymmetry characteristics, similar to ''fish'' or ''bottle''-like shapes (45), which MDA-MB-231 cells also possess when adherent. Interestingly, other studies have found that the direction of lateral migration of a deformable droplet in a ferrofluid depends on the orientation of the droplet because of uniform magnetic fields at different directions (48).…”
Section: Introductionmentioning
confidence: 99%
“…Another technique utilizes the microfluidic device's hydrodynamic properties to reduce fluctuation of flow [24], such as inertia migration [25], Dean flow [26], hydrophoresis [27], and viscoelastic [28]. The combinations of hydrodynamic forces also progressively attracted attention among the recorded passive schemes.…”
Section: 'Finger-powered' Syringe Pumpmentioning
confidence: 99%